Facile method to fabricate highly thermally conductive UHMWPE/BN composites with the segregated structure for thermal management. (27th May 2020) - Wang, Xiao; Lu, Hui; Feng, Changping; Ni, Haiying; Chen, Jun
ABSTRACT: Owing to the thermal management of polymer-based thermal conductive composites provide great performance in various applications, widespread attention has been focused on the design and fabrication of thermally conductive materials. In the work, ultrahigh molecular weight polyethylene (UHMWPE) / boron nitride (BN) composites with segregated structures were fabricated by a facile heat-treatment powder mixing method. SEM and optical images revealed that BN flakes can be tightly overlapped on the surface of UHMWPE particles by heat-treatment in the mixing process and the thermally conductive network was more continuous and homogeneous, leading to the greatly improved thermal conductivity. Laser flash thermal analyzer (LFA) demonstrated that an optimised in-plane thermal conductivity of UHMWPE/BN composites fabricated by the heat-treatment powder mixing method can reach to 9.99 W m −1 K −1 by adjusting the BN loading to 21.6 vol %. In summary, the UHMWPE/BN composite with high thermal conductivity provides excellent heat dissipation ability in the in-plane direction, which is very important for thermally conductive materials.